Evaluasi Pelaksanaan Kurikulum Tingkat Satuan Pendidikan (KTSP) Sekolah Menengah Pertama (Smp-Mts) di Kota Pekalongan Tahun 2011 - Gunawan, Muhammad Ali; Sidqi, Fajru; Haryanto, Haryanto; Wibowo, Dwi Eddy (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
This studyaims to determineanddescribeand evaluate:1)Implementation ofthe School Based Curriculum (SBC) in Junior High School in Pekalonganfromthe context, input,process,andproduct;2)the obstacles facedby schools inimplementation of School Based Curriculum (SBC) in junior High School inPekalongan.From 35Junior high schools in Pekalongan, 10 (ten)schools was taken as the samplein this study using multistagesampling technique.Data analysistechniquesused weredescriptive statisticsforthe primary data(quantitative)andqualitative for secondary data.This studyshowsthat:1)viewed from8national education standards, the implementation of School Based Curriculum (SBC)in Junior High School inPekalongan fall into thecategory of